Pertumbuhan Sukuk dan Pasaran Modal Islam di Malaysia - Sanusi, N. A.; Draman, N.; Matraji, F. (Universiti Sains Islam Malaysia, 2024)
Sukuk has attached interest especially Islamic investors since the return is based on fixed assets. Currently, the supply of sukuk has become popular in both Islamic and non-Islamic countries enabling Malaysia to take advantage, since the product has been offered in the Islamic market since the 1980s. The performance has raised a question of what is the effect of the development in sukuk market to the Malaysian Islamic capital market. Accordingly, this study identifies the role of Islamic bonds in generating the Islamic capital market growth by using the Autoregressive Distributed Lag (ARDL) approach. Based on the first quarter of 2001 to second quarter 2008, the estimated results indicate the existence of the long run relationship between the variables in the regression model.